Dynamic heart rate response to multi‐day unsupported ultra‐endurance cycle racing: a case report. Issue 2 (6th January 2019) - Brayson, Daniel; Frigiola, Alessandra; Clark, James E.
Abstract : New Findings: What is the main observation in this case? Ultra‐endurance cycle racing is known to lead to suppressed heart rates as a product of time spent racing. This case report identifies a racer who experienced this phenomenon initially, but then uniquely experienced an overall increase in heart rate late in the race. What insight does it reveal? In this case, unique chronotropic disturbances to heart rate occurred as a result of the many extreme demands of ultra‐endurance racing. Work should now focus on identifying the frequency of this response in other racers and whether the main causes are physiological, environmental or genetic in nature. Abstract: Participation in ultra‐endurance cycling events, such as the Transcontinental Race, is increasing. These extremely demanding races provide a unique opportunity for field observation of the limits of human endurance physiology and, importantly, when these limits might be exceeded and cross over into pathology. The heart is of special interest in this field, and previous data suggest that 'reverse drift' of heart rate occurs as a product of time and load in races of 24–48 h, whereas transient structural abnormalities have been observed upon completion of running ultramarathons. Here, we report a unique case of a male cyclist racing in the Transcontinental Race over an extended period of 14 days characterized by extreme workloads and a low quantity and quality of sleep. The heart rate response was dynamic over the course of the race and defined by a U‐shaped quadratic relationship. A larger scale study is required to determine the relevance of this information to the ultra‐endurance cycling community. Abstract :